MANAJEMEN PENINGKATAN MUTU PENDIDIKAN DI SMP ISLAM TERPADU DAAR AL ULUUM ASAHAN - Syafaruddin Syafaruddin; Yusuf Hadijaya; Rahmat Taufiq Siregar (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2021)
This study aims to describe the Management of Education Quality Improvement at the Islamic Junior High School Terpadu Daar Al Uluum Asahan. This research uses a qualitative research type, with a phenomenological approach. The research data collection is obtained by using observation, interview and documentation techniques. To check the validity of the data using triangulation techniques, namely credibility, transferability, dependability, and confirmability. Steps to analyze data using data analysis model Milles and Hubberman, namely reducing data, presenting data and then concluding. The results of the research are (1) Planning for improving the quality of education is carried out through meetings involving school principals, assistant principals 1 and 2, along with teachers. (2) The organization of improving the quality of education is carried out by establishing a school organizational structure and making clear job details or division of labor, then carrying out clear and directed work coordination and monitoring. (3) The implementation of improving the quality of education is carried out after the planning and organizing process. Principals, assistant principals, administrative staff and teachers have realized and implemented various planned programs, in order to achieve good, superior and quality education. (4) Supervision of improving the quality of education is carried out as an effort to observe, examine and monitor the quality of education so that efforts to improve the quality of education are being carried out in accordance with the predetermined plan, in order to achieve good, superior and quality education.Keyword: Management, Improvement, Quality of Education